2005
DOI: 10.1248/bpb.28.925
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoid from Viola hondoensis, Regulates the Expression of Matrix Metalloproteinase-1 in Human Skin Fibroblasts

Abstract: Viola hondoensis (Violaceae) distributed in southern part of Korea. In traditional medicine, the herb has been used as an expectorant, a diuretic, and an antiinflammatory for bronchitis, rheumatism, skin eruptions, and eczema.1,2) Previous phytochemical studies on Viola species have revealed them to be a rich source of cyclotides [3][4][5] and several flavone glycosides.6,7) Matrix metalloproteinases (MMPs) are a family of zinc-dependent endoproteinases that play pivotal roles in the dynamic remodeling of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…8) It has been reported that phenolics isolated from natural plants may prevent the UV-induced skin aging process by inhibiting MMP-1 expression. 30) A non-cytotoxic concentration of the DRVS extract was used in the present study to evaluate the potential inhibitory effect of phenolics on MMP-1 activated by UVA in HDF-n. The DRVS extract at 1-50 mg/L exhibited no cytotoxicity, as determined by an MTT assay (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…8) It has been reported that phenolics isolated from natural plants may prevent the UV-induced skin aging process by inhibiting MMP-1 expression. 30) A non-cytotoxic concentration of the DRVS extract was used in the present study to evaluate the potential inhibitory effect of phenolics on MMP-1 activated by UVA in HDF-n. The DRVS extract at 1-50 mg/L exhibited no cytotoxicity, as determined by an MTT assay (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…And, very recently 2 0 ,4 0 ,7-trihydroxyisoflavone (THF) was reported to reduce UV-induced MMP-1 expression, but not MMP-2, at the both mRNA and protein levels in a dosedependent manner by HSFs [12]. The aims of the present study were to examine the effect of 2 0 ,4 0 ,7-THF on UV-induced MMP-1 expression in cultured HSFs and to reveal the signaling pathway changes through which 2 0 ,4 0 ,7-THF inhibits UVinduced MMP-1 expression.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…2 0 ,4 0 ,7-THF was isolated as pure compound (purity > 99.9%) from Viola hondoensis as described previously [12]. All inhibitors (U0126, a MEK1-specific inhibitor; SP600126, a JNK-specific inhibitor; and SB203580, a p38-specific inhibitor) were purchased from Calbiochem (San Diego, CA).…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…(JNK) play a role on the regulation of MMP-1 expression under biological stimulus (15)(16)(17)(18). UVB-induced MMP-1 expression was mediated by ERK and JNK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%